Sexualidade humana e preconceito: do silêncio ao controle das condutas sexuais - Sousa, Ana Lúcia de (2012)
The present dissertation aims to analyze the construction process of sexual prejudice, based on the sexual behavior of ancient civilizations and on the guidelines of sex education in Brazil. Based on the fundamentals of dialectical materialist approach, the daily life/attitude/social behavior are a basic element as a phenomenon; and the category possibility/reality is a methodological tool seeking to understand how the basis of sex education in different societies. Thus a historical digression takes place, searching the daily life of ancient and medieval civilizations for different ways of experiencing sexuality, and searching ecclesiastical control mechanisms for the various models of punishment of those sexual behaviors considered deviant. Then, the role of science and its representatives in conflicting dialogues on sexuality is highlighted. Finally, the origin of sex education in Brazil and the guidelines of educational policies regarding the implementation of actions, which enable meeting the demand of sexual diversity in schools is presented, as well as the inclusion of topics related to sexuality and its characteristics in the curriculum of schools. Given the discussions raised here, it is clear that the vagueness, in which the debate on sexuality issues in the educational sphere lies, highlights the barriers that mark the theme, which is mostly to be found in broader approaches. The need for the adoption of posture free of taboo and prejudice seems to be an effective alternative to promote a new educational space with less discrimination and more democracy.